P.167 Documented growth of a de novo intracranial capillary hemangioma: a case report. (June 2022) - MacLellan, A; Easton, A; Pickett, G
Abstract : Background: Intracranial capillary hemangiomas are rare, particularly in adults, and diagnosis can be challenging. The literature lacks visualization of intracranial capillary hemangioma growth over time. Here we document growth of a de novo intracranial capillary hemangioma, initially interpreted radiologically as a glioma. Methods: We report a case of a 64 year old male with history of HIV, recent Lyme disease and unconfirmed prior COVID-19 infection, who presented with exhaustion and confusion. Imaging demonstrated an intra-axial high T2/FLAIR signal lesion centred in the subcortical white matter of the posterior right temporal lobe. There was faint enhancement, and a few mildly prominent vessels were seen along its anterior aspect. Imaging 2 years prior had not shown the lesion. Stereotactic biopsy was nondiagnostic. Craniotomy and resection was carried out. Results: Pathological examination and immunohistochemistry returned the diagnosis of capillary hemangioma. We review how this case adds to proposed theories of de novo intracranial capillary hemangioma growth. Our patient's co-morbidities support possible inflammation related triggers for symptomatic progression of these uncommon lesions. Conclusions: This unusual case documents the radiological appearance and progression of a de novo intracranial capillary hemangioma. It represents the first time such growth has been visualized in an adult male.